Prevalence of Diabetes and Relationship with Socioeconomic Status in the Thai Population: National Health Examination Survey, 2004–2014 - Wichai Aekplakorn; Suwat Chariyalertsak; Pattapong Kessomboon; Savitree Assanangkornchai; Surasak Taneepanichskul; Panwadee Putwatana (Journal of Diabetes Research)
Objective. To determine the prevalence and trend of diabetes, related glycemic control, and influential socioeconomic (SES) factors in the Thai population aged ≥20 years during 2004–2014. Methods. Data from the Thai National Health Examination Survey 2004, 2009, and 2014 were used. Age-adjusted prevalence was calculated, and the associations of education levels with prevalence of diabetes and glycemic control were examined using logistic regression. Results. Age-adjusted prevalence of diabetes increased from 7.7% in 2004 to 7.8% in 2009 and 9.9% in 2014 (8.9% among men and 10.8% among women). Proportions of undiagnosed diabetes were slightly decreased but remained high in 2014 (51.2% for men and 41.3% for women). Diabetes prevalence was higher among those with primary education in both sexes; however, undiagnosed diabetes was higher among women with secondary and university educations. The percentages of those treated and controlled slightly improved among men (45.9%) but not among women (36.4%). Unmet glycemic control was also higher among women with secondary education levels and among men with university-level educations. Conclusions. Epidemic diabetes continues to grow in the Thai population, particularly in individuals with lower educational attainment. Measures to detect new cases and strengthen glycemic control should be scaled up.